Exploring the Personal and Professional Realities of Parenthood and Graduate Studies - Corrente, Melissa (Alberta Journal of Educational Research, 2022)
This qualitative study using narrative inquiry as methodology explores the ways in which five parents experienced the phenomenon of graduate studies within the context of parenthood. The study uses Connelly and Clandinin’s (2006) three-dimensional narrative inquiry space to examine, deconstruct, analyze, and gain insight into dominant themes. The research question for exploration is How do graduate student parents navigate lived experiences in both parenthood and graduate studies? The inquiry broadens the field by focusing on the stories of participants as they reflect on their struggles balancing graduate work with parenthood, recognizing that although the experiences of parents are not identical, they share similar elements. Keywords: graduate studies, parenthood, academia, narrative, recommendations Cette étude qualitative utilise l'enquête narrative comme méthodologie et explore les façons dont cinq parents ont vécu le phénomène des études supérieures dans le contexte de la parentalité. L'étude utilise l'espace tridimensionnel d'enquête narrative de Connelly et Clandinin (2006) pour examiner, déconstruire, analyser et comprendre les thèmes dominants. La question de recherche à explorer est la suivante : comment les parents aux études supérieures composent-ils à la fois avec leurs expériences de parents et d’étudiants ? L'enquête élargit le champ d'investigation en se concentrant sur les récits des participants qui réfléchissent à leurs difficultés à concilier études supérieures et parentalité, en reconnaissant que si les expériences des parents ne sont pas identiques, elles partagent des éléments similaires. Mots clés : études supérieures, parentalité, milieu universitaire, récit, recommandations